The role of universities as entrepreneurship ecosystems in the era of climate change: a new theory of entrepreneurial ecology / Howard H. Frederick - Frederick, H. H. (Universiti Teknologi MARA, Perlis, 2011)
Using a systems approach to biology and ecology, and combining spatial analysis with material flows analysis, this paper aims to connect entrepreneurship, climate change and university education through the generalised notion of ‘ecosystems’. After discussing the inter-relationship of climate change and entrepreneurship in Asia, the paper goes on to discuss the general outlines of a theory of entrepreneurial ecology. Entrepreneurial ecology is a function of the econosphere embedded in the sociosphere, which are both embedded in the biosphere. People, planet and profits are highly intertwined. The focus is on ‘entrepreneurship as if the planet mattered’. This approach leads to the analysis of a ‘university-based entrepreneurship ecosystem’, a powerful new construct that can facilitate a university’s conversion into an entrepreneurial university focused on sustainability and climate change. The paper finishes with a discussion of ‘landscape analysis’ to determine the nature and scope of conversion into an entrepreneurial university.